Circular RNA hsa_circ_0000285 regulates the microRNA‐599/G‐protein subunit gamma 12 (miR‐599/GNG12) axis to promote glioma progression. Issue 3 (21st January 2022) - Liu, Fei; Duan, Chen; Han, Ya
Abstract: Objective: Glioma is the most common, rapidly progressing, lethal brain tumor. However, underlying mechanisms behind its abnormal progression remain largely unknown. This study aimed to investigate mechanism of action and effects of the hsa_circ_0000285 on glioma progression. Methods: RT‐qPCR was utilized to study RNA expression in glioma tissues and cell lines. The effects of hsa_circ_0000285 on glioma progression were studied by measuring cell proliferation and migration, apoptosis, tumor volume and weight in both glioma cells and xenograft glioma mice. The features of hsa_circ_0000285 were identified using chromatin fractionation and RNase digestion. Its mechanism of action was analyzed using bioinformatics, RNA‐binding protein immunoprecipitation, and luciferase reporter assay. Results: We found glioma tissues and cell lines were overexpressing hsa_circ_0000285. While hsa_circ_0000285 promoted cell proliferation and migration, it inhibited apoptosis in vitro. It also increased tumor volume and weight in vivo. Using bioinformatic analysis and verification experiments for studying its mechanisms, we confirmed that hsa_circ_0000285 sponged miR‐599, which negatively regulated GNG12 by binding to its mRNA. Conclusion: Hsa_circ_0000285 is overexpressed in the glioma and promotes its progression by directly regulating the miR‐599/ GNG12 axis. This novel mechanism, therefore, shows that the hsa_circ_0000285/miR‐599/ GNG12 axis may be a promising therapeutic target for glioma treatment. Abstract : Hsa_circ_0000285 promotes proliferation, migration, tumor growth of glioma ells, and inhibits apoptosis by directly regulating the miR‐599/ GNG12 axis.